Obesity, overweight and cancer mortality in the Asia-Pacific Cohort Studies Collaboration: pooled analyses of 424 519 participants - Parr, Christine Louise (2010)
BACKGROUND: Excess weight is an established risk factor for several cancers but there are sparse data from Asian populations in whom overweight and obesity is increasing rapidly and adiposity can be substantially greater for the same body mass index (BMI) compared to Caucasians. METHODS: We examined associations of adult BMI with cancer mortality (overall and 20 sites) in geographic populations from Asia and Australia/New Zealand (ANZ) within the Asia Pacific Cohort Studies Collaboration using Cox regression. Pooled data from 39 cohorts (recruitment 1961-99, median follow-up 4 years) were analyzed for 424 519 participants (77% Asian; 41% female; mean recruitment age 48 years) with individual data on BMI. FINDINGS: After excluding follow-up < 3 years, 4872 cancer deaths occurred in 401 215 participants. Hazard ratios (95% CI) for cancer sites with increased mortality risk in the obese (≥30 kg/m(2)) relative to the normal weight (18.5-24.9 kg/m(2)) were: 1.21 (1.09-1.36) for all-cause cancer (excluding lung and upper-aero digestive tract), 1.50 (1.13-1.99) for colon, 1.68 (1.06-2.67) for rectum, 1.63 (1.13-2.35) for breast in women aged ≥ 60 years, 2.62 (1.57-4.37) for ovary, 4.21 (1.89-9.39) for cervix, 1.45 (0.97-2.19) for prostate, and 1.66 (1.03-2.68) for leukaemia with the increased risk associated with a 5-unit increment in BMI ≥ 18.5 kg/m(2) ranging from 1.13 (0.91-1.40) for rectum to 1.45 (1.00-2.11) for cervix. There was little evidence of regional differences in relative risk except for oropharynx and larynx where the association was inverse in ANZ but absent in Asia. INTERPRETATION: Overweight and obese individuals in populations across the Asia-Pacific region are at significantly increased risk of mortality from cancer. Strategies to prevent overweight and obesity across Asia are required to reduce the burden of cancer expected to occur if the obesity epidemic continues. FUNDING: The APCSC has been funded by the National Health and Medical Research Council of Australia, the Health Research Council of New Zealand and Pfizer Inc., through an unrestricted medical grant.